Developing “The Mystique” Game as a Medium for Encouraging Students to Speak English (RETAIN, 2017)
Developing “The Mystique” Game as a Medium for Encouraging Students to Speak English ADI SASONGKO ROMADHON* English Education, Language and Art Faculty, State University of Surabaya LIES AMIN LESTARI* English Education, Language and Art Faculty, State University of Surabaya Abstract Speaking is considered as the most difficult skills among others. One of the reasons is the fact that teachers mostly dominate the class and give only small chance for students to speak. Such teaching atmosphere makes the student reluctant to learn to speak in English. Today, when ASEAN Economic Community effectively runs, the ability to speak in English is paramount if one wants to succeed in the ASEAN job market since English is accepted as the lingua franca among the ASEAN countries. In order to boost the student eagerness to speak in English, English teacher needs to make some efforts, among others is by creating appropriate media that can trigger students to speak. This paper aims to describe how “The Mystique”, a game intended to make students to speak, was developed. The study used the modified R&D design proposed by Gall, Gall, and Borg (2003). In addition, a discussion whether the game properly works in the classroom is also presented. Keywords: Speaking game, the mystique, research and development Abstrak Berbicara dianggap sebagai keterampilan yang paling sulit antara lain. Salah satu alasan adalah fakta bahwa sebagian besar guru mendominasi dikelas dan hanya memberikan kesempatan kecil kepada siswa untuk berbicara. Hal tersebut membuat siswa enggan untuk belajar berbicara dalam bahasa Inggris. Hari ini, ketika masyarakat ekonomi ASEAN efektif berjalan, kemampuan untuk berbicara dalam bahasa Inggris adalah yang terpenting jika ingin berhasil di pasar kerja ASEAN karena bahasa Inggris diterima sebagai bahasa penghubung di antara negara-negara ASEAN. Dalam rangka untuk meningkatkan semangat siswa untuk berbicara dalam bahasa Inggris, guru bahasa Inggris perlu melakukan beberapa upaya, antara lain adalah dengan menciptakan media yang tepat yang dapat memicu siswa untuk berbicara. Makalah ini bertujuan untuk menjelaskan bagaimana permainan